Urban Uses Put to The Test by The Covid-19 Pandemic: A Literature Review and Evidence from Algeria - Naimi Ait-Aoudia, Meriem; Khettab, Samira; Boukratem, Oumelkheir (Future Science, 2024)
The COVID-19 pandemic advent has put the spotlight back on debates about the relationship between urban planning and health-related issues, prompting a certain amount of research works worldwide. This study set out to build an analysis grid for this relationship on the basis of a literature review and apply it to the case study. To this end, our work used two levels of bibliographical analysis: the first level focused on review of research papers, which helped identify three topics related to the consequences of coronavirus disease and subsequent restrictive measures on urban uses, namely public open space, mobility, and online uses. Our study considers these latter because of their impacts on urban use and, by ricochet, on urban planning and design. The next level based exclusively on original articles review, allowed more in-depth investigations, to break down these topics into sub-topics, and to define criteria for analyzing them, which mainly include use patterns and behavioral changes and perceptions. Drawing from the insights revealed by these studies, the present article endeavors to examine the Algerian case with the aim of nourishing the debate on the resilience of cities to health crises and suggesting better guidance for urban planning and design measures.